2022
DOI: 10.1101/2022.08.29.505658
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Diversity and functional analysis of rumen and fecal microbial communities associated with dietary changes in crossbreed dairy cattle

Abstract: The objective of this study was to investigate the effect effect of varying roughage and concentrate proportions, in diet of crossbreed dairy cattle, on the composition and associated functional genes of rumen and fecal microbiota. We also explored fecal samples as a proxy for rumen liquor samples. Six crossbred dairy cattle were reared on three diets with an increasing concentrate and reducing roughage amount in three consecutive 10-day periods. After each period, individual rumen liquor and fecal samples wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 84 publications
0
1
0
Order By: Relevance
“…A significant decrease in the abundances of Methanocaldococcus , Methanococcoides , Methanocella , and Methanoregula in the HD treatment group warrants further research to determine how tanniferous material affects their abundance. A recent report ( Kibegwa et al, 2022 ) revealed that the distribution of Methanococcus in the rumen is influenced by the diet composition and its distribution tends to be greater on high roughage diets than on concentrate diets. However, the contribution of Methanocaldococcus , Methanococcoides , Methanocella , and Methanoregula to ruminal methanogenesis must be determined before concluding that their decreased abundance contributed to the lowering of methane emissions.…”
Section: Discussionmentioning
confidence: 99%
“…A significant decrease in the abundances of Methanocaldococcus , Methanococcoides , Methanocella , and Methanoregula in the HD treatment group warrants further research to determine how tanniferous material affects their abundance. A recent report ( Kibegwa et al, 2022 ) revealed that the distribution of Methanococcus in the rumen is influenced by the diet composition and its distribution tends to be greater on high roughage diets than on concentrate diets. However, the contribution of Methanocaldococcus , Methanococcoides , Methanocella , and Methanoregula to ruminal methanogenesis must be determined before concluding that their decreased abundance contributed to the lowering of methane emissions.…”
Section: Discussionmentioning
confidence: 99%